Mineralogy and Characterization of New Bentonite from Tahoua Region of Central Niger - Gourouza, M.; Harouna, M.; Zanguina, A.; Natatou, I.; Boos, A. (Asian Journal of Chemistry, 2018)
Niger imports a huge quantity of bentonite, which it uses in mining and oil exploration, but also in village hydraulics. The objective of this study is the search for a bentonite-type clay deposit on the Nigerian territory. The clay fraction of a material collected on a clay deposit of the Paleocene Garadaoua Formation in the Ullemmeden basin (central Niger) was the subject of a series of analyzes: DRX; ICP-AES; ICP-MS; ATD-ATG; IR; Adsorption/desorption of N2 at 77 K; cation exchange capacity, granulometry. DRX results corroborated by those of IR and ATD-ATG indicate that the clay minerals constituting the collected material are: montmorillonite, kaolinite and illite, with a strong predominance of montmorillonite. The mineralogical and chemical composition, the specific surface and the cation exchange capacity obtained indicate that the analyzed material is similar to that of Maghnia bentonite in Algeria.